2019
DOI: 10.3390/min9060351
|View full text |Cite
|
Sign up to set email alerts
|

Exceptional Multi Stage Mineralization of Secondary Minerals in Cavities of Flood Basalts from the Deccan Volcanic Province, India

Abstract: Flood basalts of the Deccan Volcanic Province erupted between about 67.5 to 60.5 Ma ago and reached a thickness of up to 3500 m. The main part consists of compound and simple lava flows with a tholeiitic composition erupted within 500,000 years at about 65 Ma. Within the compound lava flows, vesicles and cavities are frequent. They are filled by secondary minerals partly of well development and large size. This study presents data on the secondary mineralization including detailed field descriptions, optical, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(37 citation statements)
references
References 76 publications
1
25
0
Order By: Relevance
“…In the continental flood basalts of the Parana basin, Rb/Sr ages of celadonite (81-107 Ma) are also younger than the eruption age (127-137 Ma) indicating a time interval and a long duration of alteration between eruption and formation of celadonite [80]. Using K/Ar and Rb/Sr data on apophyllite, Ottens et al [20] determined a time interval of 24 myrs for a late hydrothermal formation of apophyllite from Savda in the Deccan Volcanic Province (India) following burial metamorphism. Środoń et al [81] report K/Ar ages of celadonite in the 500 m thick Volvyn-Brest Ediacaran continental flood basalts and distinguish two superimposed alteration processes: The Ediacaran hydrothermal alteration event related to meteoric water and the later Caledonian and/or Variscan potassic alteration.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the continental flood basalts of the Parana basin, Rb/Sr ages of celadonite (81-107 Ma) are also younger than the eruption age (127-137 Ma) indicating a time interval and a long duration of alteration between eruption and formation of celadonite [80]. Using K/Ar and Rb/Sr data on apophyllite, Ottens et al [20] determined a time interval of 24 myrs for a late hydrothermal formation of apophyllite from Savda in the Deccan Volcanic Province (India) following burial metamorphism. Środoń et al [81] report K/Ar ages of celadonite in the 500 m thick Volvyn-Brest Ediacaran continental flood basalts and distinguish two superimposed alteration processes: The Ediacaran hydrothermal alteration event related to meteoric water and the later Caledonian and/or Variscan potassic alteration.…”
Section: Discussionmentioning
confidence: 99%
“…It is also reported in the flood basalts from the Deccan Traps Volcanic Province by Ottens al. [20] as first rim-forming mineral in cavities. It also occurs in the Tertiary basalts of the Lessini Mountains of northern Italy where it is assumed to have crystallized during the deuteric cooling stage from a residual fluid with H 2 O and fluids [21].…”
Section: Introductionmentioning
confidence: 99%
“…Several investigations indicated the participation of residual magmatic fluids in the agate formation and the heating of meteoric fluids, which are necessary for the alteration of the rocks and the release of silica and other chemical elements forming secondary minerals (e.g., [22,24,37]). However, in certain occurrences such as the Paraná Continental Flood Basalt Province, Brazil or the Deccan Trap Province, India strong indications were found that the agate formation took place remarkably later than the emplacement of the surrounding volcanic host rocks [76][77][78].…”
Section: Geological Occurrences and Types Of Agatesmentioning
confidence: 99%
“…Furthermore, several organic phases were detected in agates such as carbonaceous material, solid bitumen or disordered graphite-like substances [35,[44][45][46]. Carbonates (especially calcite), iron oxides/hydroxides and clay minerals are the most frequent and present in more or less all types of agates, whereas minerals of the zeolite group are typical phases in volcanic agates [1,15,49,78]. It is noteworthy, that certain chemical elements may be present in different chemical compounds in the same agate.…”
Section: Paragenetic Minerals In Agatesmentioning
confidence: 99%
“…e massive basalt layer should act as caprock due to its fault-free and thick enough layer so that it can act as an impermeable seal [7]. e mineral composition of the Deccan basalts is dominated by the Pyroxene, Plagioclase, and Olivine mineral groups [11,[14][15][16][17]. Basalt rock formation consists mainly of the divalent cation like Ca 2+ , Mg 2+ , and Fe 2+ , which is advantageous in forming the secondary minerals.…”
Section: Introductionmentioning
confidence: 99%